Effect of Supplementation of Antioxidant Sericin in Semen Extender on Post-Thaw Sperm Quality, Oxidative Status and Fertility of Jaffarabadi Buffalo Bull Semen - Vijyeta, Hardipsinh P; Kavani, Fulabhai S; Vagh, Arshi A; Solanki, Gajendrasingh B; Vala, Karsan B; Singh, Vivek K; Dham, Arjan J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present investigation was undertaken on semen of six Jaffarabadi buffalo bulls, aged 6-8 years (n=6x6=36 ejaculates) with an objective of determining the influence of different concentrations of Sericin, viz., 0.0% control (T0), 0.25 % (T1), 0.50 % (T2), 0.75 % (T3), 1.0 % (T4) in AndroMed® extender on the quality of sperm parameters, oxidative status and fertility of cryopreserved semen. The semen samples were evaluated at pre-freeze (on dilution) and post-thaw stages. The pre-freeze sperm motility, viability, plasma membrane integrity, acrosome integrity and total antioxidant capacity of semen were significantly (p<0.05) higher with lower sperm abnormalities in control and 0.25% or 0.50% sericin supplemented extender over others, while in post-thawed semen the values of all these parameters were significantly (p<0.01) higher with lower sperm abnormalities in 0.25% followed by 0.50% Sericin groups over control and 0.75% Sericin, while 1.0% was found to be detrimental by suppressing all sperm parameters even below the control values. Lipid peroxidation (MDA production) status however did not vary much between treatment, although it was lower (p<0.05) with 0.25% and 0.50% Sericin at post-thaw stage. The first service conception rates of frozen-thawed semen with inclusion of 0.25 % and 0.50 % Sericin in extender were significantly higher (44.66±1.43 % and 42.66±1.76%) as compared to those of 0 %, 0.75%, and 1% concentrations (38.66±1.33, 29.66±1.89 and 28.66±2.13 %, respectively). Thus the study concluded that since supplementation of Sericin @ 0.25 or 0.50% (w/v) concentration in AndroMed® extender significantly improved post-thawed sperm quality parameters, oxidative status and fertility of cryoprserved Jaffarabadi buffalo semen over control and higher levels, it may be added routinely in the extender during cryopreservation of buffalo semen for better outcome.